LOAD ADAPTATION OF THE HEART RATE OF QUALIFIED WRESTLERS - Pokhachevsky, A.L.; Petrov, A.B.; Kalinin, A.V.; Baranova, M.V.; Birchenko, N.S. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify patterns of tolerance to extreme physical activity in highly skilled wrestlers of various specializations. Methods and structure of the study. A group of active athletes (24 people) took part in the scientific work. In the course of bicycle ergometric testing, the cardiorhythmogram of the pre-start, start and the entire load period was studied. Physical exercise tolerance (PE) was determined by the difference between the achieved maximum PE (Wmx) and power W1. Results and conclusions. The greatest maximum of PE is associated with an increase in the number of long-term differences in the prelaunch period (PS); maximum differences in start (ST) and 1 minute of load; minimizing small differences and increasing long-term differences during exercise (2-4 min); an increase in minimal and a decrease in long-term differences (7-9 min). The revealed patterns characterize the features of the formation of the maximum physical performance of wrestlers of various specializations, the dynamics of which probably underlies the formation of the optimal sports form.